Teachers’ Appraisal Methods and Job Performance: Learning from an Islamic Boarding School in Indonesia - Shohib, Muhammad Wildan; Othman, Azam (IIUM Journal of Educational Studies, 2019)
Abstract Purpose ‒The purpose of this study was to explore the relationship between teachers’ performance appraisal methods and teachers’ job performance and its implications to teaching and learning explicitly in the context of Islamic Boarding Schools in Gontor, East Java Indonesia, a district that has more than 10 school branches in Indonesia. Designed/methodology/approach ‒A survey method was employed to collect the data from 110 teachers who had two to five years of teaching experiences. In data analysis, the researchers had applied a two-step approach to test the measured variables representing three latent constructs namely classroom observation, lesson planning, self-appraisal, and teachers’ job performance as the criterion variable. Findings and Results ‒ The findings from descriptive analysis indicated that teachers perceived self-appraisal and classroom observation more frequently than lesson plan. Teachers viewed lesson plan as an adequate method used in teachers’ appraisal. Moreover, correlation analysis revealed that two of TPA methods namely classroom observation and self-appraisal, were positively correlated with teachers’ job performance, while lesson planning was found to have no correlation with job performance. The regression results concluded that the best predictor of teachers’ job performance was lesson planning. Research limitations/implications ‒This research only focuses on Islamic boarding school in Gontor East Java Indonesia. Originality/value: The implementation of teachers’ appraisal in Islamic Boarding School is unique to educational institutions in Muslim country such as in Indonesia. Thus, the findings could be generalized to other school branches of Gontor and schools which have similar characteristic and curriculum to those of Gontor. Keywords: Multiple regression analysis, Performance appraisal, Classroom observation, Self-appraisal, Lesson plan, Job performance, Instructional leadership, Islamic Boarding School. Paper type: Research paper